SIMPLEXITY IN WRITING ENGLISH COUPLETS FOR STUDENTS OF SMAN 19 SURABAYA - Wijaya, Kusuma; Pasopati, Rommel Utungga; Hariyono, Hariyono; Tobing, Victor Maruli Tua L.; Kartiningsih, Rindrah; Soenarko, Zahra Pramatatya; Dermawan, Zahwa Amelia Putri (Jurnal Abdi Masyarakat Multidisiplin, 2024)
This article describes the community service report that details how students at SMAN 19 Surabaya were trained to write English couplets in 2024. One type of English literary work, particularly poetry, is couplets, which are two lines of verse united in a rhyme. Writing couplets is a real example of this simplexity, where even seemingly straightforward elements can have a variety of intricate details. It is intriguing how different possibilities can be included in such brief couplet lines. According to Jeffrey Kluger, simplexity can be achieved through an exploratory strategy in qualitative research by developing a consciousness of complexity in writing and/or analyzing such straightforward topics. Expanding the notions to include any known and explorable contexts within is also necessary. By doing this, clarity may be recognized because it may represent this awareness of a system's dynamicity in even the most basic element. In this instance, highlighting specifics toward more general topics through couplet poetry helps to broaden the concept of simplexity. In conclusion, the composition of couplets by SMAN 19 Surabaya students not only illustrates the need of developing creativity in creating universal literary patterns, but also demonstrates how couplets are reflections of simplexity concepts.